Implementation of Data Parsing on Arduino Mega and NodeMCU ESP8266 for Web-Based Monitoring of E-Bike Charging Station - Nugroho, Aji; Hidayat, Mohammad Noor; Munir, Abdullah Faiq (International Journal of Frontier Technology and Engineering, 2024)
The rising trend of electric bicycles in Indonesia necessitates an efficient monitoring system for electric bicycle charging stations to ensure optimal performance and timely decision-making. This study focuses on developing and testing a web-based monitoring system utilizing Arduino Mega and NodeMCU ESP8266 for real-time data transmission and analysis. The system integrates multiple sensors, including ACS712 current sensors, DC voltage sensors, and PZEM004T sensors, to monitor key parameters such as current, voltage, power, and energy. Data parsing, a crucial process for efficient transmission, is performed on the Arduino Mega before being sent to the NodeMCU ESP8266, which then forwards the data to a web server. The research employs the Research and Development (R&D) method, encompassing stages of information gathering, system planning, implementation, and evaluation. Testing revealed that data parsing failures were due to data loss and format corruption caused by serial communication issues. Various transmission delays (0 ms, 100 ms, 200 ms, and 500 ms) were tested to evaluate their impact on data loss, communication latency, and system responsiveness. The results indicate that a 200 ms delay offers an optimal balance between data transmission frequency and system stability, with minimal data loss and stable latency. The study also explored the effects of data reception delays on the web server, highlighting that lower transmission frequencies result in more stable reception delays and better overall performance. Efficient network resource usage and system responsiveness were achieved with appropriate delay configurations.